2014
DOI: 10.1002/jctb.4593
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of complex gaseous emissions emitted by a rendering facility using a semi‐industrial biofilter

Abstract: BACKGROUND To improve process design, and scale‐up of gas biofilters, a thorough understanding of compounds degradation mechanisms within model engineering biofilters is needed. The aim of this study is then to investigate the spatial distribution of pollutants removal within an experimental semi‐industrial biofilter fed with industrial emissions from a rendering plant. RESULTS A stratification pattern of pollutants removal has been highlighted: nitrogenous compounds, esters, volatile fatty acids (VFA), alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
(41 reference statements)
1
5
0
2
Order By: Relevance
“…NH 4 + in the recirculating solution was also available as a source of N for cell growth in the biofilm. Many authors have reported the simultaneous removal of NH 3 and H 2 S, 25,27,44–47 and in the presence of a complex mixture of gases, 48 these compounds were removed in the biofilter bed near to the gas inlet in all cases 15 …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…NH 4 + in the recirculating solution was also available as a source of N for cell growth in the biofilm. Many authors have reported the simultaneous removal of NH 3 and H 2 S, 25,27,44–47 and in the presence of a complex mixture of gases, 48 these compounds were removed in the biofilter bed near to the gas inlet in all cases 15 …”
Section: Resultsmentioning
confidence: 98%
“…Several authors have reported the feasibility of using BTFs for treating different odorous gaseous emissions: sewage systems, 9 animal production buildings, 10 composting processes, 11 and animal waste treatment facilities 12 . The potentialities of biological processes for the treatment of odorous emissions from rendering operations have also been highlighted by a few authors, considering mainly biofilters 13–15 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, if the biotreatment process duration t d is insufficient to achieve the equilibrium state, the desired pollution concentration in water at the bioreactor outlet ρ 1 can be determined using the approximate formula (35). Thus, given a certain number of intervals (5)(6)(7)(8), for which in the sequential calculation by (35) the following condition is satisfied: The proposed mathematical model of the kinetics of the considered non-stationary biotreatment process, based on the approximate formula (35), can be recommended for practical calculations, as combining the desired accuracy and sufficient simplicity.…”
Section: Discussion Of the Research Results And Mathematical Modeling Of The Biotreatment Processmentioning
confidence: 99%
“…The biodetoxification method of gaseous emissions is commonly used for air deodorization from a mixture of organic matter [4], and also the accompanying inorganic odorants, such as hydrogen sulfide H 2 S on livestock farms [5]. At the same time, biodetoxification is also applied to specific emissions that contain benzene, toluene, ethylene benzene [6], carbon disulfide CS 2 [7], methyl-and dimethyl mercaptans [8], styrene [9], and organochlorine pollutants, for example, dichloromethane [10].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Biofiltration uses biological means for the deterioration of pollutants in either air or water stream. It has been applied to rectify contaminated air with volatile organic compounds (VOCs) and other gases [10,[12][13][14]. This technology is favored as a pollutant removal technique, as it has low investment and operating cost, high efficiency, reliable operating stability and low aggregate of secondary pollution [4].…”
Section: Introductionmentioning
confidence: 99%